Strategi Digitalisasi terhadap Bank Syariah untuk Meningkatkan Daya Saing - Tiara Adelia Putri; Moh. Bahrudin; Anggun Okta Fitri (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
This study aims to analyze digitalization strategies in increasing the competitiveness of Islamic banks in the modern era. Digitalization has become a critical factor in facing global competition, especially with the increasing demands of customers for fast, safe, and sharia-compliant services. Based on data from Bank Syariah Indonesia (2023), the implementation of mobile banking applications and digital services has increased the number of active customers by 25%. However, challenges such as low digital literacy, dependence on legacy systems, and the need to ensure sharia compliance are still major obstacles (Muhdar, 2023; Setiawan & Mugiyati, 2024). This study uses a qualitative approach by analyzing secondary data from accredited journals and annual reports of Islamic banks. The results of the study show that strategies such as the adoption of sharia fintech, integration of blockchain technology, use of big data analytics, and development of mobile banking applications can improve operational efficiency and customer satisfaction (Andespa, 2024; Awamleh, 2024). However, the success of digitalization is highly dependent on infrastructure readiness, human resource competence, and collaboration with sharia fintech. This study provides recommendations for Islamic banks to invest in digital infrastructure development, employee training, and product innovation in accordance with Islamic principles to increase competitiveness in the digital era.